Assessment of real-world usage of lanreotide AUTOGEL 120 in Polish acromegalic patients – results from the prospective 12-months phase of Lanro-Study - Orlewska, Ewa; Kos-Kudła, Beata; Sowiński, Jerzy; Sworczak, Krzysztof; Zgliczyński, Wojciech; Andrysiak-Mamos, Elżbieta; Babińska, Anna; Bałdys-Waligórska, Agata; Bandurska-Stankiewicz, Elżbieta; Błaut, Krzysztof; Bolko, Paweł; Foltyn, Wanda; et al. (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : To assess resource utilization and costs of treatment with lanreotide AUTOGEL 120 mg (ATG120) administered as part of routine acromegaly care in Poland. Material and methods : A multicentre, non-interventional, observational study on resource utilization in Polish acromegalic patients treated with ATG120 at 4 weeks or extended (> 4 weeks) dosing interval. The study recruited adult acromegalic patients treated medically for  1 year including at least 3 injections of ATG120. Data on dosing interval, aspects of administration, and resource utilization were collected prospectively during 12 months. Costs were calculated in PLN from the public health-care payer perspective for the year 2013. Results: 139 patients were included in the analysis. Changes in dosing regimen were reported in 14 (9.4%) patients. Combined treatment was used in 11 (8%) patients. Seventy patients (50%) received ATG120 at an extended dosing interval; the mean number of days between injections was 35.56 (SD 8.4). ATG120 was predominantly administered in an out-patient setting (77%), by health-care professionals (94%). Mean time needed for preparation and administration was 4.33 and 1.58 min, respectively, mean product wastage – 0.13 mg. Patients were predominantly treated in an out-patient setting with 7.06 physician visits/patient/ year. The most common control examinations were magnetic resonance imaging of brain and brain stem (1.36/ patient/year), ultrasound of the neck (1.35/patient/year), GH (1.69/patient/ year), glycaemia (1.12/patient/year), IGF-1 (0.84/patient/year), pituitary-thyroid axis hormone levels assessment (TSH-0.58/patient/year, T4-0.78/patient/ year). There were 0.43 hospitalizations/patient/year. For direct medical costs estimated at PLN 50 692/patient/ year the main item was the costs of ATG120 (PLN 4103.87/patient/month; 97%). The mean medical cost, excluding pharmacotherapy, was PLN 1445/patient/year (out-patient care – 49%, hospitalization – 23%, diagnostics/laboratory tests – 28%). Conclusions : These results represent the current use of ATG120 in the population of Polish acromegalic patients in a realistic clinical setting. Findings that 50% of patients could be treated with dose intervals of longer than 28 days support the potential of ATG120 to reduce the treatment burden.